2017
DOI: 10.1053/j.ajkd.2017.02.371
|View full text |Cite
|
Sign up to set email alerts
|

β-Trace Protein Assays: A Comparison Between Nephelometric and ELISA Methodologies

Abstract: advice for both acute and chronic pain. 6 Both are referenced for providers to familiarize themselves and use accordingly. Although no perfect screening tools for aberrant behaviors exist, the Opioid Risk Tool may be used to identify patients who may be at high risk for aberrant behaviors, so appropriate referral and monitoring can occur. 7 We agree that further high-quality studies are needed to refine guidelines. In the interim, we advocate using best practices for pain control and integrating patient goals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…All in all our data did not show that BTP, in addition to creatinine and cystatin C, contains significant additional information on kidney function enabling a better distinction between disease-related and age-related “physiological” change of kidney function. Besides, the accuracy of BTP measurement is lower compared to creatinine and cystatin C 25 , 26 since a certified assay standardization has not yet been successfully established 27 , a fact that may also contribute to the rather disappointing results.…”
Section: Discussionmentioning
confidence: 99%
“…All in all our data did not show that BTP, in addition to creatinine and cystatin C, contains significant additional information on kidney function enabling a better distinction between disease-related and age-related “physiological” change of kidney function. Besides, the accuracy of BTP measurement is lower compared to creatinine and cystatin C 25 , 26 since a certified assay standardization has not yet been successfully established 27 , a fact that may also contribute to the rather disappointing results.…”
Section: Discussionmentioning
confidence: 99%
“…The immunonephelometric method performed using a BNII System (Siemens Healthcare) in this study was similar to that reported in other studies. However, there are still no higher order measurement, reference materials or standardised means of measuring BTP 31 to ensure reproducibility of results across laboratory. Therefore, even though the method of measurement used in this study was similar to that reported in earlier studies, we recognise that there will be differences in the specification of analytical measurements across different instruments that can influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…17 A central aspect is the lack of standardization among available assays for both markers which results-as could be shown for BTP recently-in significant differences in BTP-based eGFRs. 18 The importance of assay standardization will be discussed further in the following.…”
Section: Determining Gfrmentioning
confidence: 99%